Comparison of Laminoplasty vs. Laminectomy for Cervical Spondylotic Myelopathy: A Systematic Review and Meta-Analysis - Zhao, Huaguo; Ren, Rong; Ma, Weihu; Xu, Song; Peng, Linrui; Zhong, Zhaoping; Zheng, Yan (Frontiers in Surgery, 2022)
Objectives: Laminoplasty (LP) and laminectomy (LC) with or without fusion are recommended as treatment procedures for cervical spondylotic myelopathy (CSM). The purpose of this study is to conduct a meta-analysis to analyze the results of CSM patients undergoing LP or LC surgery. Methods: We systematically and comprehensively searched Web of Science, Cochrane Library, PubMed, EMBASE, OVID, VIP database, Google Scholar, Chinese Bio-medicine Literature database, and China Scientific Journal Full-text database to July 2021 for randomized, controlled trials (RCTs) and observational case series that compared LP and LC in patients with CSM. The main endpoints were the surgical process, radiographic outcomes, clinical outcomes, and surgical complications. Results: A total of 20 were included the inclusion criteria in this meta-analysis (n=4348 patients). There was no significant difference in range of motion (ROM), sagittal vertical axis (SVA), Japanese Orthopedic Association (JOA), Cobb angle, visual analog scale (VAS), Japanese Orthopedic Association (JOA), cervical curvature index (CCI), Nurick score, Neck Dysfunction Index (NDI) and complications. LP was found to be superior than LC in terms of complications of C5 radiculopathy and surperficial infection. Conclusion: Our results indicate that LP can achieve better results in C5 radiculopathy and superficial infection in surgical treatment of CSM compared with LC. Further high-quality research is warranted to further verify our findings.